Prevalence of coccidiosis in Andaman local goat and its metaphylaxis in tropical island ecosystem - DE, A K; PERUMAL, P; MUNISWAMY, K; AHMED, S K ZAMIR; KUNDU, A; SUNDER, JAI; ALYETHOD, R R; RAVI, S K; BHATTACHARYA, D (The Indian Journal of Animal Sciences, 2021)
This study reports the prevalence of coccidiosis in Andaman local goat, a native goat breed of Andaman and Nicobar Islands, India. The duration of study was one year. Maximum oocyst output was seen in kids of <6 months of age in month of March followed by in November, July, August, October, September, December, May and April. More oocyst count in kids of < 6 months of age compared to those of older goats may be attributed towards higher susceptibility towards this infection. Increase of oocyst output from the month of July was due to increase in relative humidity due to high rainfall. Onset of clinical cases of caprine coccidiosis with high oocyst count was due to fodder crisis in March which imposed stress in animals. Four species of Eimeria were detected and most prevalent species in pooled sample was E. arloingi (48%), followed by E. faurei (20%) and E. pallida and E. parva (16% each) and among them E. arloingi has been seen to be associated with clinical coccidiosis of goats. Amprolium, a potent thiamine antagonist, was used to treat the infected animals with high oocyst count and the compound was found effective @ 50 mg/kg body weight which was evaluated on the basis of oocyst count, improved body weight and clinical recovery. The report is the seminal information on prevalence of coccidiosis, species richness, metaphylaxis and its effect in Andaman local goat from Andaman and Nicobar islands, an isolated insular region of India.